2005
DOI: 10.1507/endocrj.52.131
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Antagonist-induced Down-regulation of the mRNA Expression of Pituitary Receptors: Comparisons with GnRH Agonist Effects

Abstract: Abstract. In order to compare the mechanism for the down regulation of the mRNA expression of pituitary receptors induced by GnRH antagonist (GnRHant) to that by GnRH agonist (GnRHa), we examined the effects of GnRHant (Cetrorelix, 333 mg/kg/day), GnRHa (leuprolide depot, 333 mg/kg), and GnRHant combined with GnRHa on LH response to exogenous GnRH, pituitary LH content, LHb subunit mRNA, and GnRH receptor (GnRH-R) mRNA levels at 2, 5, 24, 72 hours, and 7 days after the treatment in ovariectomized rats. GnRHant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…In contrast, cetrorelix decreased FSH-beta mRNA [42]. Treatment of female rats for 7 days with GnRHag, GnRHant or their combination lead to a marked decrease in pituitary LH content [43]. This is contradictory to our finding that high concentrations of cetrorelix (100 nM) increased, whereas lower concentrations of cetrorelix did not affect the LH pool.…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast, cetrorelix decreased FSH-beta mRNA [42]. Treatment of female rats for 7 days with GnRHag, GnRHant or their combination lead to a marked decrease in pituitary LH content [43]. This is contradictory to our finding that high concentrations of cetrorelix (100 nM) increased, whereas lower concentrations of cetrorelix did not affect the LH pool.…”
Section: Discussioncontrasting
confidence: 98%
“…Bars: 500 nm events downstream of the GnRH receptor, by mechanisms referred to as receptor/post-receptor desensitization (McArdle et al, 2002;Millar et al, 2004;Naor 2009). The present study further confirmed long-lasting suppressive effects of the depot formulation of leuprorelin on biosynthesis and release of gonadotropins (Okada et al, 1991;Murase et al, 2005), by demonstrating the chronic changes in the ultrastructure of the Golgi apparatus and ER within pituitary gonadotropes. By using the chronic effects of the leuprorelin depot formulation, we further examined whether the GnRH agonist could also suppress the hypertrophic state of gonadotropes long after castration.…”
Section: Discussionsupporting
confidence: 84%
“…Suppression of hypothalamic GnRH input, either by passive anti-GnRH immunization [26] or GnRH antagonist administration [27], also reduced GnRH receptor mRNA and its protein concentrations in the pituitary, suggesting the need for sustained GnRH stimulation to maintain pituitary GnRH receptors. Reduced pituitary GnRH receptor mRNA expressions after anti-GnRH immunization indicated decreased pituitary responsiveness to GnRH stimulation.…”
Section: Discussionmentioning
confidence: 99%